Immunostimulant Effect of Vitamin-A in Channa Punctatus Challenged with Aeromonas Hydrophila: Haematological Evaluation - K. M. Syed Ali Fathima,T. Annalakshmi and B. Xavier Innocent (Journal of Applied Pharmaceutical Science)
The present study was carried out to evaluate the immunostimulant potential of vitamin A in fish. Channa punctatus was chosen for the present study and divided into 3 groups. 'A' group was uninfected, both 'B' & 'C' groups were infected with A.hydrophila and only 'C' group was injected with 0.025ml of vitamin A. Haematological parameters were analysed on 1, 2, 3, 4, 7, 14, 21 & 26th day. The total erythrocyte counts and total leucocyte counts exhibited marked increase in vitamin A administered ('C' group) fishes when compared to 'A' & 'B; groups. In differential leucocyte counts the lymphocytes and neutrophils exhibited an increasing trend in both 'B' & 'C' groups but it was significantly higher in vitamin A administered fishes. Further monocyte counts were significantly higher in 'C' group fishes and a gradual declining trend was observed. When the serum of 'C' group fishes were titrated with the pathogen in 96 well microtitre plate exhibited agglutination which further supports the increase in lymphocyte counts as a specific immune response. Thus vitamin A can be administered to improve the general resistance in fishes.
Keywords: Immunostimulant,Vitamin A,Channa punctatus,Aeromonas hydrophila,Haematology